(untitled) (Journal of Economic Research & Business Administration, 2017)
The current article deals with the new approaches of the formation of entrepreneurial potential of small business as this is one of the most important directions for the transformation of the Kazakhstani economy at the present stage. Without a small business, it is impossible to create an effective multistructure economy in Kazakhstan, to form a broad and stable middle class of owners and entrepreneurs that determine the stability of society. The growing role of small business in the economy has an objective character. Priority development of the network of small and medium-sized enterprises is necessary to address such social and economic problems as overcoming the deficit of consumer and investment resources, increasing employment of the population and its incomes, and solving environmental problems.